Palivizumab nella profilassi del virus respiratorio sinciziale: analisi di impatto sul budget del SSN italiano - Roggeri, Daniela (Farmeconomia. Health economics and therapeutic pathways, 2011)
Palivizumab is a monoclonal antibody to RSV that has been shown to significantly reduce the frequency of hospitalisations for RSV infection, in at-risk populations. However, payers are concerned about the budgetary impact of adopting palivizumab. A budget impact model was developed to estimate the financial impact of palivizumab for the prevention of severe RSV infection in at-risk populations in the Netherlands. These analyses were adapted to Italy, after a brief review of the literature on the health care system and epidemiology of RSV infection in our country. The report below outlines the methodology and analysis of the costs associated with palivizumab prophylaxis of premature infants of 33 to 35 weeks gestational age which are the at-risk subgroup eligible for prophylaxis according to Italian guidelines.